2014
DOI: 10.1111/hex.12318
|View full text |Cite
|
Sign up to set email alerts
|

Equitable access to developmental surveillance and early intervention – understanding the barriers for children from culturally and linguistically diverse (CALD) backgrounds

Abstract: Background and objective Children from culturally and linguistically diverse (CALD) backgrounds are at risk of having developmental problems go undetected prior to starting school, and missing out on early intervention. Our aim was to explore the family and service characteristics, beliefs and experiences that influence the journey of families from CALD backgrounds in accessing developmental surveillance (DS) and early intervention services in south-eastern Sydney, Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 27 publications
4
52
0
1
Order By: Relevance
“…The increased PEDS completion in English-speaking households adds to the body of research suggesting cultural and linguistic barriers to universal healthcare uptake (Carbone et al 2004;Fort Harris, Harris, & Roland;Woolfenden et al 2014), and is pertinent to ethnically diverse areas. Expanding upon the methods of disseminating PHR translations may increase DS access within CALD populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased PEDS completion in English-speaking households adds to the body of research suggesting cultural and linguistic barriers to universal healthcare uptake (Carbone et al 2004;Fort Harris, Harris, & Roland;Woolfenden et al 2014), and is pertinent to ethnically diverse areas. Expanding upon the methods of disseminating PHR translations may increase DS access within CALD populations.…”
Section: Discussionmentioning
confidence: 99%
“…While previous research has identified numerous barriers to universal healthcare uptake, little is known about the barriers specific to DS. Risk factors for reduced universal healthcare uptake include low socioeconomic status (SES) (Comino & Harris 2003;Fort Harris et al 2004), and cultural and linguistic diversity (Carbone et al 2004;Fort Harris, Harris, & Roland;Murray & Skull 2005;Schyve 2007;Woolfenden et al 2014), which represent key potential barriers to DS in ethnically diverse and economically disadvantaged regions like south western Sydney (Sydney South West Area Health Service 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For carers, services that provided transport to and from appointments were invaluable and facilitated service access. Having to wait months to access services and confusion caused by interaction with multiple service providers has also been found in an Australian study of the experiences of CALD carers accessing developmental assessment services [49] suggesting the widespread nature of these barriers. Roadblocks are particularly concerning as accessing assessment services to obtain a diagnosis is essential in being able to access support and services [54].…”
Section: Discussionmentioning
confidence: 98%
“…For instance, the role of community both facilitated and obfuscated carers’ service access. Community influence has likewise been identified in culturally and linguistically diverse (CALD) carers wherein extended family and community members sometimes presented a barrier to access by denying presence of a disability [49]. Another Australian study of CALD carers’ perceptions of preventive health care for their children found that social influence plays a key role in identification of developmental problems and the need to access services [50].…”
Section: Discussionmentioning
confidence: 99%
“…In Botany 76.3% of all children had attended pre-school or kindergarten and 50.7% had attended playgroup and/or day care before starting school [11]. Research conducted in 2013/2014 with the families from CALD backgrounds and non-government family support providers in the Botany and Randwick areas of South Eastern Sydney identified the following service provider barriers to universal developmental surveillance in preschool children [12]: a lack of understanding of the role of CFHN; child and family nongovernment (NGO) services who had no specific training in early detection of developmental and behavioural vulnerabilities in preschool children; challenges in how service providers can communicate their concerns about a child's development with the child's family; and a lack of clarity regarding referral pathways from initial concern to further assessment.…”
Section: The Settingmentioning
confidence: 99%